Novel approaches for the control of fungal pathogens - Augostine, Catheryn Rachel (2023)
Fungal pathogens are a continual threat with potential impacts on human health, agriculture, food and goods security. Despite this, currently used treatments are limited to a handful of drug or fungicide classes. The limited availability of treatment options is further challenged by growing fungal resistance, tightening legislation over drug/fungicide use and evolving public opinion. In this thesis, certain novel approaches were explored for their potential in the control of fungal pathogens of humans or crops. One approach utilised the concept of combinatorial treatments, applied specifically to synergistic interactions among natural product (NP) compounds. NPs have been questioned for their translational applications due to promiscuous activity; this study proposed the potential of synergy for potentiating antifungal activity and improving target specificity. In a high-throughput screening approach, selected NPs were screened pairwise against a wider NP chemical library. Screening of 800 NP combinations revealed 34 pairs that were potentially synergistic in their inhibitory effects on yeast growth. Moreover, scaled-up validation tests for three combinations of particular interest showed that synergy was present against several important pathogens. One synergistic combination was explored mechanistically and found to promote synergistic mitochondrial membrane depolarization and ROS formation. This work indicated the potential for synergistic NP combinations in fungal pathogen control. An additional study focussed on relationships between NP interactions and their underlying mechanisms of synergy, focusing on a particular triangle of NP interactions (involving two synergies but also no interaction). Results indicated that the NP sclareol, found to synergise with a number of other NPs, could also induce synergy between the previously non-synergistic pair of compounds. Results supported that this action of sclareol involved uncoupling of oxidative phosphorylation, which may be an activity that enables synergies against fungal pathogens more widely. An additional approach explored the potential of collateral sensitivity (CS) as a potential drug-repurposing strategy against azole-resistant Candida albicans. CS is where resistance to one drug is linked to sensitivity to another, so offering means to target drug resistant strains. Two azole-resistant clinical isolates of C. albicans showed hypersensitivity to several non-antifungal drugs, particularly aminoglycosides. The mutants were slow growers, but slow growth was not sufficient to explain the hypersensitivity, neither were the isolates’ alleles of erg11, the gene encoding the lanosterol demethylase targeted by azoles. Moreover, the hypersensitivity was not reproduced in other azole-resistant isolates. Mechanistic studies pointed to a possible role for cell wall glycosylation or integrity defects in the original two isolates. Further work expanded the search for CS compounds against azole-resistant C. albicans through a screen of a 1,280-compound library. The results did not identify any hit compounds, but reproducibility and dosage concerns meant that hit compounds could have been missed. A final approach set out to assess mechanistic bases for reported fungal anti-attachment properties of certain polymer materials. One strategy was an accelerated evolution experiment, designed to select C. albicans variants hyper-attaching to polymer. However, attachment propensity did not change, indicating resilience of the anti-attachment material properties. Another strategy examined cell wall properties that may affect anti-attachment, in C. albicans and the plant pathogen Zymoseptoria tritici. Results with selective fluorescent probes highlighted certain cell wall components that were enriched in polymer-attaching or glass-attaching cells. This offers a path for understanding cell properties important for (anti-) attachment to the polymer materials, valuable for informing design of improved polymers. Taken together the three approaches explored in this thesis offer exciting potential for bolstering efforts to control fungal pathogens, providing bases for further mechanistic and possible translational development